ANALYSIS OF THE REGIONAL FINANCIAL MANAGEMENT INFORMATION SYSTEM (SIMDA) ON THE QUALITY OF FINANCIAL REPORTS AT THE REGIONAL FINANCIAL MANAGEMENT AGENCY (BPKD) - Zulfadli, Zulfadli; Sari Dewi, Andi Ratna; Jusuf, Ardi M. (Journal of Entrepreneur, Business and Management, 2024)
The purpose of the study was to determine the application of financial simda to the quality of financial statements where this study used a quantitative approach with a sample of 40 BPKD employees with simple linear regression analysis methods, validity tests, reliability tests, t tests with the help of the SPSS 25 application.The findings of this study show that there is an influence and significance of the application of financial simda on the quality of financial statements as evidenced by the results of the hypothesis test.